Régimen de lluvias en el cultivo de hortalizas en la zona de la carretera a Santa Clara. Iquitos – 2023 - Arroyo Davila, Ariadna Angeles (2023)
The study was carried out with horticulturists on the highway to Santa Clara with the purpose of analyzing and understanding the changes in rainfall patterns that are affecting the production and quality of vegetables and how they are adapting to guarantee production. It is a non-experimental quantitative research of the exploratory type - descriptive, analytical, transversal. The primary information was obtained by applying a structured interview to 100 percent of the horticulturists in the last five years. To analyze the results, the “t” test was used for related samples of the responses of the variables Variation in the rainfall regime and Effect on the yield and quality of the crops. The results show that the majority of horticulturists perceive a significant or slight decrease in the rainfall regime, with changes in the frequency and intensity of rain, they experience intense heat and the appearance of pests in the crops, the rains are more intense and The most severe and prolonged periods of scarcity, intense rains produce floods and the appearance of pests that affect the growth of vegetables and which have an impact on the decrease in the yield of their crops and in relation to quality, they have an equitable proportion in terms of the loss of quality of their crops and products. They acknowledge having taken measures to mitigate the impacts on crops, such as greater use of insecticides and herbicides, motor pumps to irrigate crops, shading nets to protect crops from adverse weather conditions, which reflects adaptability and the search for solutions to conditions. changing climates. In the absence of policies. recognize the need for agricultural policies to help farmers adapt to climatic variations, which demonstrates the importance of government intervention to address the climatic challenges they face in their vegetable crops. Finally, for the horticulturists of the Highway to Santa Clara. According to the “t” test, it shows that the variation in the rainfall regime has a significant impact on the yield and quality of the crops, so the alternative hypothesis of the study is accepted.